Piezoelectric ceramic for high-temperature driver and method for manufacturing the same
Patent Information
- Application Number
- CN202611393128.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-13
AI Technical Summary
例如中国专利CN108585836B公开了一种BNT基压电陶瓷,其组成为0.93Bi0.5Na0.5TiO3-0.07BaTiO3:(0.1%-0.5%MoO3),通过MoO3掺杂改善了BNT-BT陶瓷压电性能较低和漏电流高的问题,但该专利仅采用单一Mo元素掺杂进行体相改性,其压电常数提升有限,难以满足高温环境的使用需求
[0027]在上述范围下,有效抑制高温烧结过程中铋元素的挥发散失,维持压电陶瓷基体完整晶体结构,降低压电陶瓷漏电流与高温介电损耗,保障掺杂改性效果充分发挥,避免离子价态失衡造成压电性能衰减。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to a piezoelectric ceramic for high-temperature actuators and its preparation method, belonging to the field of piezoelectric ceramic technology. Background Technology
[0002] Bismuth sodium titanate ((Bi0.5Na0.5)TiO3, abbreviated as BNT)-based piezoelectric ceramics, as typical lead-free and environmentally friendly piezoelectric materials, effectively solve the environmental pollution problem caused by lead volatilization during the production and use of traditional lead-based piezoelectric ceramics (such as the PZT series), and have become a research hotspot in the field of piezoelectric materials in recent years. However, pure BNT ceramics have defects such as high coercivity, difficulty in polarization, and the need to improve piezoelectric performance. In addition, their surface is susceptible to wear and corrosion, and their performance is easily affected by the environment, which limits their large-scale application in high-end fields.
[0003] To improve the performance of BNT-based piezoelectric ceramics, researchers both domestically and internationally have generally adopted elemental doping modification techniques. By introducing different types of doping elements into the BNT matrix, their crystal structure, phase composition, and defect distribution are controlled, thereby optimizing their piezoelectric, dielectric, and mechanical properties. Alternatively, they can combine them with other matrices to enhance the performance of piezoelectric ceramics. For example, Chinese patent CN108585836B discloses a BNT-based piezoelectric ceramic with a composition of 0.93Bi0.5Na0.5TiO3-0.07BaTiO3:(0.1%-0.5%MoO3). MoO3 doping improves the low piezoelectric performance and high leakage current of BNT-BT ceramics. However, this patent only uses Mo as a single element for bulk phase modification, resulting in limited improvement in piezoelectric constant, which is insufficient to meet the requirements for high-temperature applications. Another Chinese patent, CN104944943A, discloses a BNT-based lead-free electrostrictive material with luminescent properties. Its chemical formula is (1-x)(Bi0.5Na0.5)TiO3-xM-yR (where M is a specific perovskite material and R is a rare earth element). Although the introduction of rare earth elements achieves the combination of luminescent properties and electrostrictive performance, and the published document states that it has good temperature stability under conditions of 25-180℃, the piezoelectric ceramic material in the above patent cannot maintain good stability in high-temperature environments (>200℃).
[0004] Therefore, there is an urgent need for a composite piezoelectric ceramic that improves the overall piezoelectric, dielectric, and mechanical properties while maintaining good temperature stability at high temperatures. Summary of the Invention
[0005] To address the aforementioned issues, a piezoelectric ceramic for high-temperature actuators is provided. The piezoelectric ceramic matrix is synergistically modified by multi-element doping and CeO2-Ta2O5 composite modifiers. This not only optimizes the high-temperature resistance of the piezoelectric ceramic matrix itself through element doping but also enhances its high-temperature performance through CeO2-Ta2O5 composite modifiers.
[0006] One aspect of this application provides a piezoelectric ceramic for a high-temperature actuator with the chemical formula: 0.89(Bi) 1-x- z Ce x Sm z ) 0.5 Na 0.5 TiO3-0.06Bi 0.5 K 0.5-y La y TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-pwt%(CeO2-Ta2O5), where 0.02≤x≤0.05, 0.01≤z≤0.03, 0.02≤y≤0.04, 0.5≤p≤1.5, 0.89(Bi 1-x- z Ce x Sm z ) 0.5 Na 0.5 TiO3-0.06Bi 0.5 K 0.5-y La y TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3 is the piezoelectric ceramic matrix, and (CeO2-Ta2O5) is the composite modifier; the mass ratio of CeO2 to Ta2O5 is 1:(0.8-1.2).
[0007] Under the above settings, by doping the A site of the BNT base with Ce and Sm, and simultaneously doping the A site of the BKT with La, the Curie temperature and high-temperature structural stability of the piezoelectric ceramic can be significantly improved. This effectively suppresses the volatilization of bismuth at high temperatures, reduces the thermal relaxation of electric domains at high temperatures, and ensures stable piezoelectric output displacement and high driving accuracy of the actuator in the high-temperature range. At the same time, the addition of composite modifiers can form a uniform and stable modified phase at the grain boundaries. This not only improves the high-temperature insulation of the piezoelectric ceramic and reduces high-temperature dielectric loss and leakage current, avoiding severe heat generation and performance drift under high-temperature driving, but also prevents excessive modification phase from hindering polarization and domain flipping, ensuring that the piezoelectric ceramic has excellent piezoelectric response speed and driving sensitivity.
[0008] Preferably, 0.03≤x≤0.04, 0.02≤z≤0.03, 0.03≤y≤0.04, and 0.5≤p≤1.5.
[0009] Within the aforementioned range, firstly, it can fully leverage the lattice regulation effect of rare earth ions, effectively refining ceramic grains and suppressing abnormal grain growth, while also maximally suppressing bismuth volatilization during high-temperature sintering and high-temperature service, significantly improving the stability of the perovskite phase structure, and significantly increasing the Curie temperature of piezoelectric ceramics, thus preventing phase transitions at high temperatures that could lead to driving performance failure; secondly, it effectively optimizes the degree of lattice distortion, significantly reduces the coercive field of the ceramic, and increases the activity of domain flipping, enabling the piezoelectric ceramic to possess a higher piezoelectric constant, ensuring large driving displacement, fast response speed, and high driving accuracy under high-temperature conditions, while also significantly reducing high-temperature dielectric loss and leakage current, and reducing the heat generation phenomenon during driver operation.
[0010] In addition, the composite modifier can be evenly distributed at the grain boundaries, further filling the grain boundary pores and strengthening the grain boundary bonding force. This can not only help improve the stability of high-temperature service, but also avoid the accumulation of additives that hinder the polarization process and do not affect the inherent driving response capability of the matrix.
[0011] Optionally, the chemical formula is: 0.89(Bi) 0.47 Ce 0.02 Sm 0.01 ) 0.5 Na 0.5 TiO3-0.06Bi 0.5 K 0.47 La 0.03 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-1wt%(CeO2-Ta2O5).
[0012] Optionally, the mass ratio of CeO2 to Ta2O5 is 1:1.
[0013] Under the above ratio, the modification advantages of the two oxides can be fully complemented, and their ionic valence and lattice compatibility are better. They can form a uniform, dense and stable modified phase at the grain boundaries of piezoelectric ceramics. This not only relies on CeO2 to effectively suppress the volatilization of bismuth in the matrix at high temperatures and rationally control the oxygen vacancy concentration in the system to reduce dielectric loss and leakage current, but also uses Ta2O5 to improve the high-temperature structural strength and thermal shock resistance of piezoelectric ceramics. At the same time, it effectively refines the grains and improves the overall density and mechanical fatigue resistance of piezoelectric ceramics.
[0014] Another aspect of this application provides a method for preparing piezoelectric ceramics for high-temperature actuators, comprising the following steps: (1) Weigh the raw materials according to the chemical formula ratio, then put them into a ball mill, add anhydrous ethanol and glacial acetic acid, stir and mix at 50-60℃ for 3-4 hours, dry and sieve to obtain the mixture; (2) The mixture is pre-fired once, then CeO2 and Ta2O5 are added for a second pre-fire, cooled, ground, dried and sieved to obtain the pre-made material; (3) Add binder to the prefabricated material, stir and mix evenly, then press and shape to obtain green blank; (4) The green blanks are degreased and sintered in a weak oxygen-enriched atmosphere and then cooled to room temperature to obtain sintered material; (5) Electrodes are plated onto the sintered material, dried, and then polarized to obtain piezoelectric ceramics for high-temperature actuators.
[0015] The above preparation method can effectively improve the dispersion uniformity of various powder raw materials, eliminate the agglomeration of raw materials, and ensure that the components of each dopant element are fully mixed, laying a good foundation for subsequent uniform doping of the crystal lattice. First, the piezoelectric ceramic matrix raw material is pre-fired at low temperature to initially synthesize the matrix structure, and then a (CeO2-Ta2O5) composite modifier is added for a second pre-fired process. This allows the composite modifier components to uniformly penetrate into the grain boundaries of the piezoelectric ceramic matrix, which avoids the large-scale volatilization of bismuth caused by direct sintering at high temperature, and also achieves full fusion between the piezoelectric ceramic matrix and the composite modifier, thereby controlling the crystal structure.
[0016] Subsequently, debinding and sintering are carried out simultaneously in a weakly oxygen-enriched atmosphere. This not only removes the organic binder within the green body, preventing residual impurities from affecting electrical properties, but also stabilizes the ionic valence state inside the piezoelectric ceramic and solidifies Ce³. + Ta 5+ Its stable existence further enhances the high-temperature resistance and thermal structural stability of piezoelectric ceramics, effectively reducing high-temperature dielectric loss.
[0017] Optionally, the preheating in step (2) includes the following steps: heating to 450-480℃ at a heating rate of 3-5℃ / min and holding for 1-2 hours.
[0018] Under the above treatment, the raw material powder can be heated evenly, which promotes the initial solid-state reaction of each piezoelectric ceramic matrix raw material, initially forming a stable precursor structure, fixing the basic phase composition of the matrix in advance, effectively reducing the volatilization and loss of bismuth element in subsequent processes, and uniformly dispersing it inside the matrix system. This not only ensures the precise and controllable matrix composition ratio, but also reduces the reaction difficulty of subsequent secondary pre-firing and high-temperature sintering, and alleviates the lattice distortion stress during later high-temperature sintering.
[0019] Optionally, the secondary preheating in step (2) includes the following steps: heating to 600-640℃ at a heating rate of 2-4℃ / min and holding for 2-4 hours.
[0020] Under the above treatment, the composite modifier can be fully impregnated and bonded to the piezoelectric ceramic mixture, promoting the uniform dispersion of the components in the composite modifier into the intergranular gaps, achieving good integration with the piezoelectric ceramic matrix, and further stabilizing the lattice structure. Long-term heat preservation can fully complete the phase transition reaction, effectively inhibit the premature volatilization and loss of bismuth, optimize the grain growth state, eliminate residual reaction stress inside the powder, reduce the risk of cracking during subsequent high-temperature sintering, and significantly improve the powder activity and molding sintering compatibility.
[0021] Optionally, the degreasing process in step (4) includes the following steps: heating to 220-240℃ and holding for 1-2 hours, then heating to 380-400℃ and holding for 1-3 hours.
[0022] Under the above treatment, low-boiling-point organic solvents and free water in the green body can be slowly removed, avoiding rapid volatilization of organic components that could cause cracking, bubbling, and loose structure in the green body. Further heating can fully decompose and remove high-boiling-point organic substances such as binders in the green body, thereby removing organic components, reducing impurity residues, and further improving the density, insulation performance, and high-temperature stability of the finished ceramic.
[0023] Optionally, the sintering process in step (4) includes the following steps: heating to 980-1030℃ and holding for 4-5 hours.
[0024] Within this temperature range, the grains in the piezoelectric ceramic matrix can grow and develop fully and be densely arranged, significantly improving the overall density of the piezoelectric ceramic and effectively closing internal micropores and grain boundary defects. Under the weak oxygen-enriched atmosphere, this sintering condition can fully complete the solid-phase reaction and effectively suppress the volatilization and loss of bismuth at high temperatures. At the same time, it is conducive to the uniform solid solution of composite modification additives at the grain boundaries, strengthening the grain boundary bonding strength, stabilizing the ion valence state, and reasonably controlling the oxygen vacancy content, thereby improving the high-temperature structural strength of the piezoelectric ceramic.
[0025] Optionally, the polarization treatment includes the following steps: heating to 120°C at 3-4°C / min, increasing the electric field strength from 0 kV / mm to 4 kV / mm at this polarization temperature and maintaining it for 2-4 min, then increasing it from 4 kV / mm to 8 kV / mm and maintaining it for 3-5 min; finally increasing it from 8 kV / mm to 12 kV / mm and maintaining it for 20-30 min, continuing to maintain it at 12 kV / mm, cooling to 60°C at 2-4°C / min, turning off the polarization electric field, and then cooling to room temperature to complete the polarization treatment.
[0026] Optionally, the volume fraction of O2 in the weakly oxygen-enriched atmosphere is 22%–25%.
[0027] Within the above range, the volatilization and loss of bismuth during high-temperature sintering are effectively suppressed, the complete crystal structure of the piezoelectric ceramic matrix is maintained, the leakage current and high-temperature dielectric loss of the piezoelectric ceramic are reduced, the doping modification effect is fully utilized, and the piezoelectric performance is avoided due to the imbalance of ion valence state.
[0028] The beneficial effects of this application include, but are not limited to: 1. The piezoelectric ceramic for high-temperature actuators according to this application, by limiting the doping ratio and segmented pre-sintering process, combined with a weak oxygen-enriched sintering atmosphere, can effectively suppress the volatilization of bismuth element at high temperature, stabilize the valence state and lattice occupation of each doped ion, improve the overall thermal stability and high-temperature resistance of the piezoelectric ceramic, and can be adapted to the harsh high-temperature working environment of high-temperature actuators.
[0029] 2. The preparation method of piezoelectric ceramics for high-temperature actuators according to this application can gradually remove organic impurities and eliminate stress in the green body, effectively avoiding defects such as cracking, deformation, and porosity in the product. It can not only ensure the integrity of the green body forming, but also improve the sintering density, so that the piezoelectric ceramic grains are evenly distributed, and the overall mechanical strength and structural uniformity are greatly improved.
[0030] 3. The piezoelectric ceramic for high-temperature actuators according to this application can reduce dielectric loss and leakage current, optimize domain switching capability, improve piezoelectric response efficiency and driving accuracy, and enable piezoelectric ceramics to still have the advantages of rapid response, stable displacement output and slow performance decay under high-temperature conditions. Detailed Implementation
[0031] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0032] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application were all purchased commercially.
[0033] Unless otherwise specified, the methods used in the embodiments and comparative examples of this application are conventional methods in the prior art.
[0034] Example 1 This embodiment relates to a piezoelectric ceramic for a high-temperature actuator, with the chemical formula: 0.89(Bi) 0.485 Ce 0.01 Sm 0.005 Na 0.5 TiO3-0.06Bi 0.5 K 0.048 La 0.02 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-0.5wt%(CeO2-Ta2O5), the mass ratio of CeO2 to Ta2O5 in the composite modifier is 1:0.8; The method for preparing the piezoelectric ceramic for the high-temperature actuator includes the following steps: (1) According to the chemical formula 0.89(Bi) 0.485 Ce 0.01 Sm 0.005 Na 0.5 TiO3-0.06Bi 0.5 K 0.048 La 0.02 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 Weigh out Bi2O3, Na2CO3, TiO2, CeO2, Sm2O3, K2CO3, La2O3, BaCO3, and Nb2O5 in the following proportions: NbO3, and place them in a ball mill. Add 0.7 times the amount of anhydrous ethanol and 0.3 times the amount of glacial acetic acid. Stir and mix at 50°C for 4 hours, and dry at 80°C for 6 hours in a constant temperature drying oven. After passing through an 80-mesh sieve, the mixture is obtained. (2) The mixture is heated to 450°C at a heating rate of 3°C / min and held for 2 hours for a first pre-calcination. Then CeO2 and Ta2O5 are added and the mixture is heated to 600°C at a heating rate of 2°C / min and held for 4 hours for a second pre-calcination. After cooling to room temperature, it is ground and dried at 80°C in a constant temperature drying oven for 2 hours. Then it is passed through an 80-mesh sieve to obtain the pre-made material. (3) Add 1.5wt% of polyvinyl alcohol solution (concentration of 8wt%) of the total mass of the prefabricated material to the prefabricated material, stir and mix evenly, and then press at 28MPa for 20S to form a green body; (4) The green blank is heated to 220°C at 2°C / min and held for 2 hours in an atmosphere of nitrogen and oxygen mixture with O2 volume fraction of 22%. Then it is heated to 380°C at 3°C / min and held for 3 hours for degreasing treatment. Then it is heated to 980°C at 3°C / min and held for 5 hours for sintering treatment. Then it is cooled to room temperature at 2°C / min to obtain sintered material. (5) Grind and clean the sintered material, coat the upper and lower surfaces with conductive electrodes (silver), dry in a constant temperature drying oven at 80°C for 6 hours, treat at 800°C for 5 seconds, raise the temperature to 120°C at 3°C / min, at this polarization temperature, raise the electric field strength from 0 kV / mm to 4 kV / mm and maintain for 2 min, then raise it from 4 kV / mm to 8 kV / mm and maintain for 3 min; finally raise it from 8 kV / mm to 12 kV / mm and maintain for 20 min, continue to maintain 12 kV / mm, lower the temperature to 60°C at 2°C / min, turn off the polarization electric field, and then cool to room temperature to complete the polarization treatment and obtain the piezoelectric ceramic for high temperature actuator.
[0035] Example 2 This embodiment relates to a piezoelectric ceramic for a high-temperature actuator, with the chemical formula: 0.89(Bi) 0.460 Ce 0.025 Sm 0.015 Na 0.5 TiO3-0.06Bi 0.5 K 0.46 La 0.04 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-1.5wt%(CeO2-Ta2O5), the mass ratio of CeO2 to Ta2O5 in the composite modifier is 1:1.2; The method for preparing the piezoelectric ceramic for the high-temperature actuator includes the following steps: (1) According to the chemical formula 0.89(Bi) 0.460 Ce 0.025 Sm 0.015 Na 0.5 TiO3-0.06Bi 0.5 K 0.46 La 0.04 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 Weigh out Bi2O3, Na2CO3, TiO2, CeO2, Sm2O3, K2CO3, La2O3, BaCO3, and Nb2O5 according to the NbO3 formula. Add 0.7 times the amount of anhydrous ethanol and 0.3 times the amount of glacial acetic acid. Then put it into a ball mill (ball mill speed 300 r / min), stir and mix at 60℃ for 3 h, dry at 80℃ for 6 h in a constant temperature drying oven, and obtain the mixture by passing it through an 80 mesh sieve. (2) The mixture is heated to 480°C at a heating rate of 5°C / min and held for 1 hour for a first pre-calcination. Then CeO2 and Ta2O5 are added and the mixture is heated to 640°C at a heating rate of 4°C / min and held for 2 hours for a second pre-calcination. After cooling to room temperature, it is ground and dried at 80°C in a constant temperature drying oven for 2 hours. Then it is passed through an 80-mesh sieve to obtain the pre-made material. (3) Add 1.5wt% of polyvinyl alcohol solution (concentration of 8wt%) of the total mass of the prefabricated material to the prefabricated material, stir and mix evenly, and then press at 28MPa for 20S to form a green body; (4) The green blank is heated to 240°C at 2°C / min and held for 1 hour in an atmosphere of nitrogen and oxygen mixture with O2 volume fraction of 25%. Then it is heated to 400°C at 3°C / min and held for 1 hour for degreasing treatment. Then it is heated to 1030°C at 3°C / min and held for 4 hours for sintering treatment. Then it is cooled to room temperature at 2°C / min to obtain sintered material. (5) Grind and clean the sintered material, coat the upper and lower surfaces with conductive electrodes (silver), dry in a constant temperature drying oven at 80°C for 6 hours, treat at 800°C for 5 seconds, raise the temperature to 120°C at 4°C / min, at this polarization temperature, raise the electric field strength from 0 kV / mm to 4 kV / mm and maintain for 4 min, then raise it from 4 kV / mm to 8 kV / mm and maintain for 5 min; finally raise it from 8 kV / mm to 12 kV / mm and maintain for 30 min, continue to maintain 12 kV / mm, lower the temperature to 60°C at 4°C / min, turn off the polarization electric field, and then cool to room temperature to complete the polarization treatment and obtain the piezoelectric ceramic for high temperature actuator.
[0036] Example 3 This embodiment relates to a piezoelectric ceramic for a high-temperature actuator, with the chemical formula: 0.89(Bi) 0.47 Ce 0.02 Sm 0.01 ) 0.5 Na 0.5 TiO3-0.06Bi 0.5 K 0.47 La 0.03 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-1wt%(CeO2-Ta2O5), the mass ratio of CeO2 to Ta2O5 in the composite modifier is 1:1; The method for preparing the piezoelectric ceramic for the high-temperature actuator includes the following steps: (1) According to the chemical formula 0.89(Bi) 0.47 Ce 0.02 Sm 0.01 ) 0.5 Na 0.5 TiO3-0.06Bi 0.5 K 0.47 La 0.03 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 Weigh out Bi2O3, Na2CO3, TiO2, CeO2, Sm2O3, K2CO3, La2O3, BaCO3, and Nb2O5 according to the NbO3 formula. Add 0.7 times the amount of anhydrous ethanol and 0.3 times the amount of glacial acetic acid. Then put it into a ball mill (ball mill speed 300 r / min), stir and mix at 55℃ for 2.5 h, dry at 80℃ for 6 h in a constant temperature drying oven, and obtain the mixture by passing it through an 80 mesh sieve. (2) The mixture is heated to 460°C at a heating rate of 4°C / min and held for 1.5h for a first pre-calcination. Then CeO2 and Ta2O5 are added and the temperature is increased to 620°C at a heating rate of 3°C / min based on the first pre-calcination temperature. It is held for 3h for a second pre-calcination. After cooling to room temperature, it is ground and dried at 80°C in a constant temperature drying oven for 2h. Then it is passed through an 80-mesh sieve to obtain the pre-made material. (3) Add 1.5wt% of polyvinyl alcohol solution (concentration of 8wt%) of the total mass of the prefabricated material to the prefabricated material, stir and mix evenly, and then press at 28MPa for 20S to form a green body; (4) The green blank is heated to 230°C at 2°C / min and held for 1.5h in an atmosphere of nitrogen and oxygen mixture with O2 volume fraction of 24%. Then it is heated to 390°C at 3°C / min and held for 2h for degreasing treatment. Then it is heated to 1000°C at 3°C / min and held for 4.5h for sintering treatment. Then it is cooled to room temperature at 2°C / min to obtain sintered material. (5) Grind and clean the sintered material, coat the upper and lower surfaces with conductive electrodes (silver), dry in a constant temperature drying oven at 80°C for 6 hours, treat at 800°C for 5 seconds, raise the temperature to 120°C at 3°C / min, at this polarization temperature, raise the electric field strength from 0 kV / mm to 4 kV / mm and maintain for 3 min, then raise it from 4 kV / mm to 8 kV / mm and maintain for 4 min; finally raise it from 8 kV / mm to 12 kV / mm and maintain for 25 min, continue to maintain 12 kV / mm, lower the temperature to 60°C at 3°C / min, turn off the polarization electric field, and then cool to room temperature to complete the polarization treatment and obtain the piezoelectric ceramic for high temperature actuator.
[0037] Example 4 The difference between this embodiment and embodiment 3 is that the temperature of the first pre-firing in step (2) is 500°C, while the rest is the same as in embodiment 3.
[0038] Example 5 The difference between this embodiment and embodiment 3 is that the temperature of the second pre-firing in step (2) is 550°C, while the rest is the same as in embodiment 3.
[0039] Example 6 The difference between this embodiment and embodiment 3 is that in step (4), the temperature is raised to 390℃ at 2℃ / min and kept at that temperature for 2 hours for degreasing treatment, while the rest is the same as in embodiment 3.
[0040] Example 7 The difference between this embodiment and embodiment 3 is that in step (4), the weakly oxygen-enriched atmosphere is replaced with a mixture of nitrogen and oxygen with an oxygen content of 10%, while the rest is the same as in embodiment 3.
[0041] Example 8 The difference between this embodiment and embodiment 3 is that in step (5), the polarization treatment is to raise the temperature to 120°C at a rate of 3°C / min. At this polarization temperature, the electric field strength increases from 0 kV / mm to 12 kV / mm and is maintained for 25 min. The rest is the same as in embodiment 3.
[0042] Comparative Example 1 The difference between this comparative example and Example 3 is that the chemical formula is: 0.89(Bi 0.44 Ce 0.05 Sm 0.01 Na 0.5 TiO3-0.06Bi 0.5 K 0.47 La 0.03 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-1wt%(CeO2-Ta2O5), the rest is the same as in Example 3.
[0043] Comparative Example 2 The difference between this comparative example and Example 3 is that the chemical formula is 0.89 (Bi). 0.48 Ce 0.02 Na 0.5 TiO3-0.06Bi 0.5 K 0.47 La 0.03 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-1wt%(CeO2-Ta2O5), the rest is the same as in Example 3.
[0044] Comparative Example 3 The difference between this comparative example and Example 3 is that the chemical formula is: 0.89(Bi 0.49 Sm 0.01 Na 0.5 TiO3-0.06Bi 0.5 K 0.47 La 0.03 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-1wt%(CeO2-Ta2O5), the rest is the same as in Example 3.
[0045] Comparative Example 4 The difference between this comparative example and Example 3 is that the chemical formula is 0.89 (Bi). 0.47 Ce 0.02 Sm 0.01 Na0.5 TiO3-0.06Bi 0.5 K 0.5 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-1wt%(CeO2-Ta2O5), the rest is the same as in Example 3.
[0046] Comparative Example 5 The difference between this comparative example and Example 3 is that: 0.89 (Bi) 0.47 Ce 0.02 Sm 0.01 Na 0.5 TiO3-0.06Bi 0.5 K 0.47 La 0.03 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-1wt%(CeO2), the rest is the same as in Example 3.
[0047] Comparative Example 6 The difference between this comparative example and Example 3 is that the mass ratio of CeO2 to Ta2O5 is 1:2, while the rest is the same as in Example 3.
[0048] Test Example 1 The piezoelectric ceramics in Examples 1-8 and Comparative Examples 1-6 were subjected to the following tests, and the test results are shown in Table 1. (1) Leakage current test method: Refer to the test method in GB / T3389.2-2019 and conduct the test under an electric field of 4kV / cm; (2) Relative density test method: The relative density of the piezoelectric ceramic sample was tested using the Archimedes method.
[0049] Table 1
[0050] Test Example 2 The piezoelectric ceramics in Examples 1-8 and Comparative Examples 1-6 were subjected to the following tests: (1) Test method for dielectric constant εr: The capacitance of the piezoelectric ceramic sample was tested at 1 kHz using a TH2810B+ capacitance meter, and the dielectric constant εr was calculated using the following formula: εr=14.4×C×t / Φ 2 Equation (1) In the formula: C is the capacitance, pF; t is the thickness of the piezoelectric ceramic sample, cm; Φ is the diameter of the circular silver electrode of the piezoelectric ceramic sample, cm.
[0051] (2) Test method for dielectric loss tanδ: The loss value of the piezoelectric ceramic sample was tested at 1KHz using a TH2810B+ type capacitance tester.
[0052] (3) Piezoelectric constant d 33 Test method: Using ZJ-5AN quasi-static piezoelectric constant d 33 The testing instrument is used to test the piezoelectric ceramic sample.
[0053] (4) Curie temperature test method: Place the piezoelectric ceramic sample in a high-temperature oven and connect it to the TH2826 test bridge with an external lead wire. Starting from room temperature, the temperature is continuously increased, and the capacitance at the high temperature is recorded. The dielectric constant is calculated from the capacitance to obtain the relationship between the dielectric constant and temperature. As the temperature increases, the dielectric constant will reach a maximum value. The temperature corresponding to the maximum value of the dielectric constant is the Curie point of the piezoelectric ceramic.
[0054] (5) Test method for the rate of change of piezoelectric constant d33: Heat the piezoelectric ceramic sample to 150℃, keep it at that temperature for 30 min and then test its d33 value. Calculate the rate of change of d33 value relative to room temperature. The smaller the absolute value of the rate of change of piezoelectric constant d33, the better the temperature stability.
[0055] The rate of change of piezoelectric constant d33 = (C1-C2)C1 / ×100%, where C1 is the d33 value measured at room temperature and C2 is the d33 value measured at 150℃.
[0056] Table 2
[0057] According to the data in Tables 1 and 2, the electrical performance of Example 3 is the best. Examples 1 and 2 are within the optimal protection range of the present application and therefore also have good electrical performance.
[0058] In Example 4, the high temperature during the first pre-firing process exacerbates the excessive agglomeration of powder particles and surface lattice passivation. Furthermore, the high temperature causes the mixed powder to react too quickly, resulting in premature coarsening of powder grains. Ultimately, this leads to a decrease in the powder's diffusion capacity during the sintering stage, which can easily cause problems such as incomplete sintering, insufficient density, and residual pores, thereby affecting the various electrical properties of the piezoelectric ceramic.
[0059] In Example 5, the secondary pre-calcination temperature was relatively low, resulting in incomplete solid solution of the powder, residual impurities, numerous gas-generating pores, and hindered densification. It also increased piezoelectric loss and leakage current. 33 Temperatures in Curie have dropped.
[0060] Example 6 has a high degreasing temperature. At this temperature, the organic binder decomposes rapidly and produces gas, which easily forms a large number of pores. At the same time, the organic matter carbonizes and leaves carbonaceous impurities. The pores reduce the density of the ceramic. The presence of pores and residual carbon increases both leakage current and dielectric loss. The presence of pores also breaks the piezoelectric matrix, which in turn reduces the piezoelectric constant and Curie temperature, resulting in poorer temperature stability of the piezoelectric ceramic.
[0061] In Example 7, sintering was carried out in an atmosphere with low oxygen content. The piezoelectric ceramic lattice was prone to generating a large number of oxygen vacancies and forming pores and trace metal impurities. The oxygen vacancies would generate a large number of conductive charge carriers, causing the leakage current to increase. At the same time, the dielectric loss and Curie temperature would increase, and the piezoelectric constant and dielectric constant would decrease.
[0062] In Example 8, during the polarization process, the internal thermal stress and electric field stress of the billet increase rapidly and instantaneously, which can easily induce microcracks, reduce the effective density, and significantly increase the leakage current. The crack interface brings a large amount of relaxation loss, which increases the dielectric loss and reduces the piezoelectric constant and dielectric constant. The presence of cracks causes the internal non-uniform stress and lattice defects to change the perovskite distortion and reduce the Curie temperature.
[0063] In Comparative Example 1, the high Ce doping content leads to excessive donor doping and surplus free electrons, resulting in an increase in carrier concentration, leakage current, impurity phases, grain boundary defects, and excess carriers, which increase dielectric loss. Excessive lattice distortion pins domains, and impurity phases fragment the piezoelectric matrix, reducing the piezoelectric constant and dielectric constant. At the same time, a high doping content severely weakens the stability of the perovskite structure due to lattice distortion, causing the Curie temperature to shift to lower temperatures, exacerbating the temperature drift of the material, and worsening its temperature stability.
[0064] In Comparative Example 2, without Sm doping, Bi volatilization intensifies at high temperatures, leading to a significant increase in lattice oxygen vacancy concentration. This eliminates the grain refinement suppression effect, resulting in coarse and uneven grains, increased grain boundary defects, and decreased density. The large number of oxygen vacancies provides conductive charge carriers, significantly increasing leakage current and consequently increasing dielectric loss, while reducing piezoelectric constant and dielectric constant.
[0065] In Comparative Example 3, without Ce doping, the grains became abnormally coarsened, the sintering pores increased, the density decreased, the leakage current and dielectric loss increased significantly, the piezoelectric constant and dielectric constant decreased, and the Curie temperature decreased.
[0066] Comparative Example 4 does not contain La, so it cannot rely on La³⁺. + Stabilizing the A-site composition of the BKT phase and suppressing the high-temperature volatilization of potassium bismuth leads to an increase in the concentration of oxygen vacancies in the lattice, resulting in coarsening and size inhomogeneity of the grains, an increase in sintering pores, and a decrease in density. A large number of oxygen vacancies form conductive pathways, significantly increasing leakage current. The superposition of oxygen vacancy conductivity loss, coarse grain domain wall loss, and pore interface polarization loss leads to an increase in dielectric loss, a decrease in piezoelectric constant and dielectric constant, and a decrease in Curie temperature.
[0067] In Comparative Example 5, without the addition of Ta2O5, it is impossible to form a synergistic effect with CeO2, and it is difficult to suppress abnormal grain growth at high temperatures. The concentration of oxygen vacancies in the lattice increases, the number of pores in the sintered blank increases, and the density decreases. The increase of oxygen vacancies and low-valence titanium ion carriers in the system makes it easy to form conductive channels, resulting in increased leakage current and a significant increase in dielectric loss.
[0068] In Comparative Example 6, the CeO2-Ta2O5 ratio was unbalanced, failing to exert a synergistic effect, and the excess Ta... 5+ The entry of B sites into perovskites triggers excessive donor doping, lattice distortion exceeds the tolerance threshold, and grain size differentiation intensifies. At the same time, the excess Ta component exceeds the solid solution limit, resulting in the precipitation of tantalum-rich impurity phases. The porosity inside the sintering chamber increases, leading to a decrease in density. The excess free electrons and impurity phase interface defects together construct multiple conductive pathways, resulting in a significant increase in leakage current, a substantial increase in dielectric loss, and a significant decrease in piezoelectric constant.
[0069] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.
Claims
1. A piezoelectric ceramic for a high-temperature actuator, characterized in that, The chemical formula is: 0.89(Bi) 1-x-z Ce x Sm z ) 0.5 Na 0.5 TiO3-0.06Bi 0.5 K 0.5-y La y TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-pwt%(CeO2-Ta2O5), where 0.02≤x≤0.05, 0.01≤z≤0.03, 0.02≤y≤0.04, 0.5≤p≤1.5, 0.89(Bi 1-x-z Ce x Sm z ) 0.5 Na 0.5 TiO3-0.06Bi 0.5 K 0.5-y La y TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3 is the piezoelectric ceramic matrix, and (CeO2-Ta2O5) is the composite modifier; the mass ratio of CeO2 to Ta2O5 is 1:(0.8-1.2).
2. The piezoelectric ceramic for a high-temperature actuator according to claim 1, characterized in that, 0.03≤x≤0.04, 0.02≤z≤0.03, 0.03≤y≤0.04, 0.5≤p≤1.
5.
3. The piezoelectric ceramic for a high-temperature actuator according to claim 1, characterized in that, The chemical formula is: 0.89(Bi) 0.47 Ce 0.02 Sm 0.01 Na 0.5 TiO3-0.06Bi 0.5 K 0.47 La 0.03 TiO3-0.03BaTiO3-0.02K 0.48 Na 0.52 NbO3-1wt%(CeO2-Ta2O5).
4. The piezoelectric ceramic for a high-temperature actuator according to claim 3, characterized in that, The mass ratio of CeO2 to Ta2O5 is 1:
1.
5. The method for preparing piezoelectric ceramics for high-temperature actuators according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Weigh the raw materials according to the chemical formula ratio, add anhydrous ethanol and glacial acetic acid, then put them into a ball mill and stir and mix at 50-60℃ for 3-4 hours. After drying and sieving, the mixture is obtained. (2) The mixture is pre-fired once, then CeO2 and Ta2O5 are added for a second pre-fired, cooled, ground, dried and sieved to obtain the pre-made material; (3) Add binder to the prefabricated material, stir and mix evenly, then press and shape to obtain green body; (4) The green blank is degreased and sintered in a weak oxygen-enriched atmosphere and then cooled to room temperature to obtain sintered material; (5) Electrodes are plated onto the sintered material, dried, and then polarized to obtain piezoelectric ceramics for high-temperature actuators.
6. The method for preparing piezoelectric ceramics for high-temperature actuators according to claim 5, characterized in that, The first preheating in step (2) includes the following steps: heating to 450-480℃ at a heating rate of 3-5℃ / min and holding for 1-2 hours.
7. The method for preparing piezoelectric ceramics for high-temperature actuators according to claim 5, characterized in that, The secondary preheating in step (2) includes the following steps: heating to 600-640℃ at a heating rate of 2-4℃ / min and holding for 2-4 hours.
8. The method for preparing piezoelectric ceramics for high-temperature actuators according to claim 5, characterized in that, The degreasing process in step (4) includes the following steps: heating to 220-240℃ and holding for 1-2 hours, then heating to 380-400℃ and holding for 1-3 hours.
9. The method for preparing piezoelectric ceramics for high-temperature actuators according to claim 5, characterized in that, The sintering process in step (4) includes the following steps: heating to 980-1030℃ and holding for 4-5 hours.
10. The method for preparing piezoelectric ceramics for high-temperature actuators according to claim 5, characterized in that, The volume fraction of O2 in the weakly oxygen-enriched atmosphere is 22%–25%.
Citation Information
Patent Citations
BNT-base lead-free electrostriction material with light-emitting characteristic and preparation method thereof
CN104944943A
A BNT-based piezoelectric ceramic and its preparation method
CN108585836B